Proceedings of the 3rd Asia Pacific International Conference of Management and Business Science (AICMBS 2019) 2020
DOI: 10.2991/aebmr.k.200410.034
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Frauds on the Indonesian Islamic Banks

Abstract: This paper examines the issue of fraud and discusses two ways to minimize frauds in Indonesian Islamic banks; they are compliance to sharia principles in muamalah and profit distribution management by Islamic bank managers to fulfill their obligation to their customers. By observing eight Islamic banks from 2013 to 2017, a total of 40 data were collected from the banks' websites, and they were analyzed using Sobel test. The results show that sharia compliance and profit distribution management are able to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have shown Shariah corporate governance's urgency in preventing fraud (Ghoniyah and Hartono, 2020; Yusmansyah et al , 2020; Alam et al , 2021). Shariah compliance and profit distribution management are two key factors in reducing fraud in Islamic banks (Ghoniyah, Mutamimah and Amilahaq, 2020). Moreover, some attributes of the Shariah Supervisory Board (SSB), like the number of SSB members, the frequency of SSB meetings and their expertise in accounting, finance or economics, are determining factors in reducing financial statement fraud in Islamic banks (Mukhibad et al , 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Several studies have shown Shariah corporate governance's urgency in preventing fraud (Ghoniyah and Hartono, 2020; Yusmansyah et al , 2020; Alam et al , 2021). Shariah compliance and profit distribution management are two key factors in reducing fraud in Islamic banks (Ghoniyah, Mutamimah and Amilahaq, 2020). Moreover, some attributes of the Shariah Supervisory Board (SSB), like the number of SSB members, the frequency of SSB meetings and their expertise in accounting, finance or economics, are determining factors in reducing financial statement fraud in Islamic banks (Mukhibad et al , 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Menurut Rusono (2019) Konsumen yang pertama kali melakukan pembelian suatu produk biasanya melihat kualitas produk tersebut dari wujud luar, melalui kualitas konsumen akan melakukan pembelian terhadap produk yang di belinya. Menurut Prawirosentono dalam Ghoniyah et al, (2020) Kualitas produk adalah suatu kondisi fisik, sifat, dan kegunaan suatu barang yang dapat memberi kepuasaan konsumen secara fisik maupun psikologis, sesuai dengan nilai uang yang di keluarkan. Oleh karena itu Perum Bulog membuat standar beras dalam hal pengadaan besar untuk di perjual belikan ke konsumen, standar beras ini di buat agar untuk menjaga mutu kualitas beras hingga ke tangan konsumen.…”
Section: Pendahuluanunclassified
“…They also make goals in accordance with Islamic principles as the main vision. It is called falah or victory of the world and hereafter (Biyantoro & Ghoniyah, 2019;Ghoniyah & Hartono, 2019b;Indonesian Bankers Association, 2014, p. 5). This emphasizes the bank's task which must not only seek personal gain but also for the welfare of all creatures including the environment (maqashid syariah).…”
Section: Islamic Bank and Conventional Bankmentioning
confidence: 99%
“…Meanwhile, if the bank's profit is low and NPF is high, it can be concluded that the company's performance is not good enough. Thus, they cannot make a major contribution to sustainable development goals, and the low profit achieved is because of the bad condition of business in society (Ghoniyah & Hartono, 2019a;Ghoniyah et al, 2020).…”
Section: Relationship Between Financing Quality and Profitability On mentioning
confidence: 99%